Parabacteroides distasonis-Derived Outer Membrane Vesicles Enhance Antitumor Immunity Against Colon Tumors by Modulating CXCL10 and CD8+ T Cells - Liang R; Li P; Yang N; Xiao X; Gong J; Zhang X; Bai Y; Chen Y; Xie Z; Liao Q (Dove Medical Press, 2024)
Rongyao Liang,1,* Pei Li,1,2,* Na Yang,1 Xiaoyi Xiao,1 Jing Gong,1 Xingyuan Zhang,1 Yunuan Bai,1 Yanlong Chen,1 Zhiyong Xie,3 Qiongfeng Liao1 1School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province, People's Republic of China; 2Science and Technology Innovation Center, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province, People's Republic of China; 3School of Pharmaceutical Sciences (Shenzhen), Sun Yat-sen University, Shenzhen, Guangdong Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiongfeng Liao, School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China, Tel +86 2039358081, Email zyfxliao@gzucm.edu.cn Zhiyong Xie, School of Pharmaceutical Sciences (Shenzhen), Sun Yat-sen University, Guangzhou, 510006, People's Republic of China, Tel +86 075523260207, Email xiezhy@mail.sysu.edu.cnPurpose: Given the potent immunostimulatory effects of bacterial outer membrane vesicles (OMVs) and the significant anti-colon tumor properties of Parabacteroides distasonis (Pd), this study aimed to elucidate the role and potential mechanisms of Pd-derived OMVs (Pd-OMVs) against colon cancer.Methods: This study isolated and purified Pd-OMVs from Pd cultures and assessed their characteristics. The effects of Pd-OMVs on CT26 cell uptake, proliferation, and invasion were investigated in vitro. In vivo, a CT26 colon tumor model was used to investigate the anti-colon tumor effects and underlying mechanisms of Pd-OMVs. Finally, we evaluated the biosafety of Pd-OMVs.Results: Purified Pd-OMVs had a uniform cup-shaped structure with an average size of 165.5 nm and a zeta potential of approximately − 9.56 mV, and their proteins were associated with pathways related to immunity and apoptosis. In vitro experiments demonstrated that CT26 cells internalized the Pd-OMVs, resulting in a significant decrease in their proliferation and invasion abilities. Further in vivo studies confirmed the accumulation of Pd-OMVs in tumor tissues, which significantly inhibited the growth of colon tumors. Mechanistically, Pd-OMVs increased the expression of CXCL10, promoting infiltration of CD8+ T cells into tumor tissues and expression of pro-inflammatory factors TNF-α, IL-1β, and IL-6. Notably, Pd-OMVs demonstrated a high level of biosafety.Conclusion: This paper elucidates that Pd-OMVs can exert significant anti-colon tumor effects by upregulating the expression of the chemokine CXCL10, thereby increasing the infiltration of CD8+ T cells into tumors and enhancing antitumor immune responses. This suggests that Pd-OMVs may be developed as a novel nanoscale potent immunostimulant with great potential for application in tumor immunotherapy. As well as developed as a novel nano-delivery carrier for combination with other antitumor drugs. Keywords: Parabacteroides distasonis, outer membrane vesicles, colon tumor, CXCL10, CD8+ T cells